Dual-responsive synthetic gene circuit for dynamic biologic drug delivery via inflammatory and circadian signaling pathways - Amanda Cimino; Fiona Pat; Omolabake Oyebamiji; Christine T.N. Pham; Erik D. Herzog; Farshid Guilak (Journal of Biological Engineering)
Abstract Background Engineered cells provide versatile tools for precise, tunable drug delivery, especially when synthetic stimulus-responsive gene circuits are incorporated. In many complex disease conditions, endogenous pathologic signals such as inflammation can vary dynamically over different time scales. For example, in autoimmune conditions such as rheumatoid arthritis or juvenile idiopathic arthritis, local (joint) and systemic inflammatory signals fluctuate daily, peaking in the early morning, but can also persist over long periods of time, triggering flare-ups that can last weeks to months. However, treatment with disease-modifying anti-rheumatic drugs is typically provided at continuous high doses, regardless of disease activity and without consideration for levels of inflammatory signals. In previous studies, we have developed cell-based drug delivery systems that can automatically address the different scales of flares using either chronogenetic circuits (i.e., clock gene-responsive elements) that can be tuned for optimal drug delivery to dampen circadian variations in inflammatory levels or inflammation-responsive circuits (i.e., NF-κB-sensitive elements) that can respond to sustained arthritis flares on demand with proportional synthesis of drug. The goal of this study was to develop a novel dual-responsive synthetic gene circuit that responds to both circadian and inflammatory inputs using OR-gate logic for both daily timed therapeutic output and enhanced therapeutic output during chronic inflammatory conditions. Results We developed a synthetic gene circuit driven by tandem inflammatory NF-κB and circadian E’-box response elements. When engineered into induced pluripotent stem cells that were chondrogenically differentiated, the gene circuit demonstrated basal-level circadian output with enhanced stimulus-responsive output during an inflammatory challenge shown by bioluminescence monitoring. Similarly, this system exhibited enhanced therapeutic levels of biologic drug interleukin-1 receptor antagonist (IL-1Ra) during an inflammatory challenge in differentiated cartilage pellets. This dual-responsive therapeutic gene circuit mitigated both the inflammatory response as measured by bioluminescence reporter output and tissue-level degradation during conditions mimicking an arthritic flare. Conclusions The dual-responsive synthetic gene circuit developed herein responds to input cues from two key homeostatic transcriptional networks, enabling dynamic and tunable output. This proof-of-concept approach has the potential to match drug delivery to disease activity for optimal outcomes that addresses the complex environment of inflammatory arthritis.